Nathaniel Shepard Armstrong Price papers - Price, Nathaniel Shepard Armstrong, 1841-1919.; Killam, Ruth Price, 1916-2012.
Memoir of Price pertaining to his Civil War service in Company E, 17th Ohio Infantry Regiment, and to the time he spent in Andersonville Prison, Andersonville, Ga., as a Confederate prisoner of war. Price describes his capture on September 20, 1863; the physical surroundings of Andersonville Prison; flooding in the camp; aspects of daily life such as the distribution of food and medical service; the guards; the "raiders" and "regulators"; and execution of the leaders of the "raiders." Also documents Price's imprisonment in Atlanta and Dalton, Ga., and Danville and Richmond, Va., as well as his escape and recapture while in Danville, Va. Other subjects include the Battle of Camp Wildcat, Laurel County, Ky.; the Tullahoma Campaign, Tennessee; and the Battle of Chickamauga, Georgia. Includes a typewritten transcript of the diary by Price's granddaughter, Ruth Price Killam, and notes concerning her grandfather and the transcription. Also includes two photographs of Price and an annotated photograph and map of Andersonville Prison.
Union Army soldier.
Collection material in English.
Keywords: United States. -- Army. -- Ohio Infantry Regiment, 17th (1861-1865). -- Company E; Andersonville Prison; Chickamauga, Battle of, Ga., 1863.; Prisoners of war -- Confederate States of America; Prisoners of war -- Georgia -- Andersonville; Andersonville (Ga.) -- History -- Civil War, 1861-1865.; Atlanta (Ga.) -- History -- Civil War, 1861-1865.; Dalton (Ga.) -- History -- Civil War, 1861-1865.; Danville (Va.) -- History -- Civil War, 1861-1865.; Georgia -- History -- Civil War, 1861-1865.; Kentucky -- History -- Civil War, 1861-1865.; Laurel County (Ky.) -- History -- Civil War, 1861-1865.; Ohio -- History -- Civil War, 1861-1865.; Richmond (Va.) -- History -- Civil War, 1861-1865.; Tennessee -- History -- Civil War, 1861-1865.; Tullahoma Region (Tenn.) -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- Civil War, 1861-1865 -- Prisoners and prisons; Virginia -- History -- Civil War, 1861-1865.; Soldiers